2021
DOI: 10.2807/1560-7917.es.2021.26.23.2100447
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 B.1.351 lineage (VOC β) is outgrowing the B.1.1.7 lineage (VOC α) in some French regions in April 2021

Abstract: To assess SARS-CoV-2 variants spread, we analysed 36,590 variant-specific reverse-transcription-PCR tests performed on samples from 12 April–7 May 2021 in France. In this period, contrarily to January–March 2021, variants of concern (VOC) β (B.1.351 lineage) and/or γ (P.1 lineage) had a significant transmission advantage over VOC α (B.1.1.7 lineage) in Île-de-France (15.8%; 95% confidence interval (CI): 15.5–16.2) and Hauts-de-France (17.3%; 95% CI: 15.9–18.7) regions. This is consistent with VOC β’s immune ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
3
21
1
Order By: Relevance
“…The estimated transmission advantages of 79% (95% CI: 52-110%) the Delta variant over the Alpha variant are in line with that estimated in the UK [7] and from the analysis of the number of variant sequences in the GISAID database [17]. Consistent with our earlier findings from April 2021 [13], we also find that Beta/ Gamma/Eta variants have a transmission advantage over the Alpha variant.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The estimated transmission advantages of 79% (95% CI: 52-110%) the Delta variant over the Alpha variant are in line with that estimated in the UK [7] and from the analysis of the number of variant sequences in the GISAID database [17]. Consistent with our earlier findings from April 2021 [13], we also find that Beta/ Gamma/Eta variants have a transmission advantage over the Alpha variant.…”
Section: Discussionsupporting
confidence: 90%
“…In these three regions, we also found a significant transmission advantage of the Delta variant over the Beta/Gamma/Eta variants (Figure 1B). Finally, consistently with our previous results [13], we find that Beta/ Gamma/Eta variants have a significant, but smaller, transmission advantage over the Alpha variant in these regions (Figure 1C). Transmission advantages tend to decrease with time (Supplementary Figure S3), which could be linked to a delay in collecting the cases or a change in selection pressures.…”
Section: Transmission Advantagessupporting
confidence: 92%
See 2 more Smart Citations
“…SARS-CoV-2 N501Y.V1 and N501Y.V2 lineages rapidly replaced the original strain, suggesting the mutations of these variants may be related to increased transmissibility. Preliminary studies have shown that N501Y.V1 and N501Y.V2 lineages have high transmission efficiency and immune escape from neutralizing antibodies than the original strain ( Galloway et al., 2021 ; Hoffmann et al., 2021 ; Roquebert et al., 2021 ). However, the transmission properties and biological characteristics of these variants remain elusive.…”
Section: Introductionmentioning
confidence: 99%